2017
DOI: 10.4244/eij-d-15-00254
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of acute kidney injury after transcatheter aortic valve implantation: a systematic review and meta-analysis

Abstract: The reason for the occurrence of AKI was multifactorial, including baseline characteristics, procedure-related and post-TAVI factors. It appeared that even stage 1 AKI exerted detrimental effects on survival within one year, and AKI was also independently linked to mortality beyond three years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 46 publications
7
36
0
2
Order By: Relevance
“…Second, the incidence of AKI post-TAVR (24-38%) in our study is in line with previously reported frequencies [5,6]. Third, although our results did not demonstrate a correlation between angiogram AKI and TAVR AKI, they did identify baseline renal function and contrast volume as independent predictors of post-TAVR AKI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Second, the incidence of AKI post-TAVR (24-38%) in our study is in line with previously reported frequencies [5,6]. Third, although our results did not demonstrate a correlation between angiogram AKI and TAVR AKI, they did identify baseline renal function and contrast volume as independent predictors of post-TAVR AKI.…”
Section: Discussionsupporting
confidence: 91%
“…Although physician experience and technology are improving, procedural complications remain a common issue affecting patient outcomes. Specifically, acute kidney injury (AKI) occurs in as many as 8.3-58% of patients, and has been shown to be associated with increased 30-day and three-year post-TAVR mortality rates [5,6]. A recent systematic review confirmed this relationship by demonstrating that developing an AKI, results in a 2-6 fold increase in post-TAVR mortality [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study proved that bleeding complications and blood transfusion were predictors of AKI [27]. In addition, the detrimental effect of red blood cell transfusion on AKI and long-term survival was associated with an increased number of transfusions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-regression plot (meta-regression line with 95% confidence interval curves) of the principal analysis (as-treated population) of the primary end point: risk differences in 1-year all-cause mortality (between transcatheter aortic valve implantation and surgical aortic valve replacement) on Society of Thoracic Surgeons Predicted Risk of Mortality (STS-PROM) score et al [16] demonstrated, in their meta-analysis of 35 studies with a total of 13,256 patients undergoing TAVI, that the aggravating severity of AKI was progressively associated with short-term all-cause mortality (univariate OR of 30-day mortality for stage 1, 3.41; for stage 2, 4.0; for stage 3, 11.02; univariate OR of 1-year mortality for stage 1, 1.95; stage 2, 2.82; stage 3, 7.34). Even after controlling confounders, AKI was independently associated with a higher risk of both 30-day [multivariate hazard ratio (HR) 2.12; 95% CI 1.59-2.83] and ≥3-year all-cause mortality (multivariate HR 1.37; 95% CI 1.27-1.48) [16]. Faster and better recovery of left ventricular function [17] and less frequent pulmonary complications [18] after TAVI than after SAVR may also explain the present results.…”
Section: Figmentioning
confidence: 99%